'I'm Here as a Social Worker': A Qualitative Study of Immigration Status Issues and Safeguarding Children in Private Fostering Arrangements in the UK. (17th July 2019) - Wells, Karen
Abstract : Private fostering of non‐citizen children in the UK has become a focus of child protection social work since the Laming report into the death of Victoria Climbié. This paper reports on a qualitative study that aimed to understand children's experiences of private fostering and social work practice. The study involved interviews with social workers and privately fostered children, reviews of advice line calls to Children and Families Across Borders and a review of safeguarding reports from London boroughs. It found that many children who present as 'privately fostered' have been in effect abandoned by their parents and are living with strangers. While the homes that they live in may be safe, insecure immigration status renders children vulnerable and, if not regularised, will lead to complicated and stalled transitions to adulthood. The key findings of this study are that children whose parents are not resident in the UK are treated as privately fostered, but the underlying premise of private fostering legislation, which is that the parent retains meaningful responsibility for the child, is often not in place. 'Reports on a qualitative study that aimed to understand children's experiences of private fostering and social work practice' Key Practitioner Messages: Privately fostered children may have insecure immigration status. Social workers should consider regularising immigration status for privately fostered children as part of safeguarding. If a child's parents are not resident in the UK, social workers should consider whether the local authority has a duty to make arrangements for him/her to have a safe home.